NILAI-NILAI PENDIDIKAN ISLAM DALAM SURAH LUKMAN - Garancang, Sabaruddin (Universitas Islam Negeri Alauddin Makassar, 2016)
The concept of education in the Qur'an principally establishes the communities based on faith in God Almighty. It aims to improve the quality of human resources which in turn can provide valuable contribution in achieving the common goals; just and prosperous society blessed by Alah SWT. Then, the concept of education Lukman al-Hakim contains several topics; (1) faith and monotheism coaching; it can be seen in verse 13 of Surah Luqman as described in the previous discussion. (2) Worship coaching; this can be seen in verse 17 of Surah Luqman. The implementation of the order for the children persuasively encourages and guides them to pray. (3) Character building; it can be seen in verse 14, 15, 18 and 19. Moral is the implementation of faith and all forms of behavior. Among examples of the morals taught to his son are; 1) the morals of children to his parents (verse 14); 2) the morals of children to others (verses 18, 19); 3) the morals of children to her appearance (verse 19); and 4) personality and social issues development can be seen in verse 16. The formation of personality occurs in the long term ranging from birth until the age of 21 years. Finally, personality formation is closely related to the development of faith and morals.